The impact of gymnastics training on body coordination - Aleksic Veljkovic, A.; Herodek, K.; Stojanovic, M.; Milcic, L.; Zivcic Markovic, K. (International Scientific Congress Slovenian Gymnastics Federation, 2019)
Artistic gymnastics is a sport that demands performance of different elements on the gymnastics apparatus, but also maintaining balance while preserving the aesthetic value of the exercise. Also, gymnastics is an important activity for the healthy growth and development of children`s coordination, balance and other motor abilities. In this sport, one can distinguish a path from natural movement to very complex acrobatic figures. The coordination and balance are the most important motoric features that decide about learning skills and results of young categories in aesthetic sports. Twenty three girls (7.11±.93 age) from Niš (Serbia), participated in the present study. They were informed of the nature and possible inconveniences associated with the study. Ethical approval was granted by the University Ethics Committee. Children participated in 60 minutes per training three times per week during four months. Trainings included activities based on fundamental movement skills and also learning basic motor skills from artistic gymnastics. Data was collected in December 2017. and second testing was in march 2018. For the measurement of the childrens bilateral coordination and balance were used two subtests of the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2). Results for the pre-test post-test values of the experimental programme showed significant improvements in five testing variables of coordination: Touching Nose with Index Fingers - Eyes Closed, Jumping Jacks, Jumping in Place - Opposite Sides Synchronized, Tapping Feet and Fingers - Opposite sides synchronized, and Bilateral Coordination Total (p<0.05). There was no statistically significant difference between the Jumping in Place - Same Sides Synchronized, Pivoting Thumbs and Index Fingers and Tapping Feet and Fingers - Same Sides Synchronized.